CENTRAL ASIAN COUNTRIES AND THE UNITED STATES: UPS AND DOWNS IN THEIR RELATIONSHIPS - ABDULLO, Rashid (CENTRAL ASIA AND THE CAUCASUS, 2005)
The events that took place in Central Asia in the first half of 2005 changed the geopolitical situation in the region to a certain extent. I have in mind the political crisis and the regime change in Kyrgyzstan, the clashes in the Uzbek city of Andijan, the request the SCO summit addressed to the United States to specify the terms for withdrawing its bases from the region, and finally Tashkent’s official demand that the United States should remove its base from Khanabad in 180 days. This was the first time in the post-Soviet era that Washington was confronted with political difficulties in the region.One of the factors behind the new developments is the changed attitude toward the United States obvious both at the top and at the grassroots level: the original welcome has gradually waned to be replaced with a guarded attitude. The region has never been overly enthusiastic about the United States: in the first couple of years of their independence, the former Soviet Central Asian republics still looked at the U.S. from the Soviet viewpoint. At all times, however, local ideas about the United States differed greatly from those in the European part of the U.S.S.R.Most of the local people are Muslims, therefore a Western lifestyle was at no time accepted as an alternative to the Soviet way of life. The values were different, even though there were exceptions to this rule too